Acute Care Utilization in Patients With Concurrent Mental Health and Complex Chronic Medical Conditions. (October 2016) - Abernathy, Karen; Zhang, Jingwen; Mauldin, Patrick; Moran, William; Abernathy, Mac; Brownfield, Elisha; Davis, Kimberly
Objectives: Patients with coexisting mental health disorder and chronic disease are more at risk for poor outcomes, including increased acute care utilization. This study was performed to assess the association of mental health disorders on acute care utilization (emergency department [ED] use, hospitalization, and rehospitalization within 30 days) using disease clustering.Methods: A retrospective cohort analysis was performed on 10 408 patients. Adult patients >18 years of age were included in the study if they were seen at least twice in University Internal Medicine primary care clinic at the Medical University of South Carolina from October 10, 2010 through September 30, 2013. The main outcome measure was a count of acute care use (hospital or ED). A linear regression model was used to fit a predictive model for ED and hospital utilization, and agglomerative hierarchical clustering was used to identify patients with similar comorbidities.Results: Covariates associated with increased risk of ED and hospital utilization include non-white race (rate ratio [RR] = 1.35, P < .0001), resident physician (RR = 1.30, P < .0001), and public insurance (RR = 1.56, P < .0001). Patients within the multiple chronic conditions (MCC), chronic obstructive pulmonary disease (COPD)/asthma, or renal disease clusters had 1.80 ( P < .0001), 1.50 ( P < .0001), and 2.57 ( P < .0001) times, respectively, the amount of predicted utilization compared with healthy patients, whereas patients with a mental health diagnosis had 1.41 ( P < .0001) times the predicted utilization. There was a significant association with increased utilization in patients with coexisting mental health disorder and chronic disease within the COPD/asthma (RR = 1.20, P = .0038), renal disease (RR = 1.27, P < .0001), and MCC (RR = 1.34, P < .0001) clusters.Conclusions: Patients with co-occurring chronic medical conditions and mental health disorders have higher rates of acute care utilization compared with patients with chronic medical conditions alone. Improving access to mental health care at the primary care clinic may have a positive impact on utilization.